2012
DOI: 10.5897/ajps11.163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of time of harvest on physiological maturity and kenaf (Hibiscus canabinus) seed quality

Abstract: Field experiments were carried out between July and December 2010 and 2011 at research station of the Institute of Agricultural Research and Training, Obafemi Awolowo University, Moor Plantation, Ibadan, to determine the effects of time of harvesting on kenaf seed physiological maturity and quality. Kenaf seed of 10 genotypes were collected at seven harvesting periods. Seeds were harvested at 5 day interval from 15 to 45 days after flowering (DAF). Significant variation was observed in all the kenaf genotypes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 19 publications
0
9
0
2
Order By: Relevance
“…Harvesting crops at early maturity stage usually resulted in yield loss due to high seed moisture content, high percentage of immature seeds and low 1000 seed weight; while delayed harvesting resulted in more seeds were filled and consequently, average seed weight increased [32,33]. Seeds gradually attain viability and vigor during the developmental process as seed dry weight is accumulated during maturity [11]. The increase in dry weight of the seeds towards maturity reflects the accumulation of nonstructural carbohydrates, reducing sugars and fibre, relative to seed moisture content which showed a sharp fall [34].…”
Section: Thousand Seed Massmentioning
confidence: 99%
See 2 more Smart Citations
“…Harvesting crops at early maturity stage usually resulted in yield loss due to high seed moisture content, high percentage of immature seeds and low 1000 seed weight; while delayed harvesting resulted in more seeds were filled and consequently, average seed weight increased [32,33]. Seeds gradually attain viability and vigor during the developmental process as seed dry weight is accumulated during maturity [11]. The increase in dry weight of the seeds towards maturity reflects the accumulation of nonstructural carbohydrates, reducing sugars and fibre, relative to seed moisture content which showed a sharp fall [34].…”
Section: Thousand Seed Massmentioning
confidence: 99%
“…Seed development is the period between fertilization and maximum fresh weight accumulation and seed maturation begins at the end of seed development and continues till harvest [10]. Studies on seed development and physiological maturity become important because seeds should be harvested at proper time to ensure their quality in terms of viability and vigor [11]. Seed quality can be limited by environmental conditions both before and after physiological maturity, the stage of development at which the seed possesses its maximum dry mass [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…crude oils mainly for their pharmaceutical applications in the synthesis of drugs and could be either exploited in cosmetic products as a primary ingredient in soap, lotions, and creams manufacturing as well as in cleaning agents for detergents making. [17] The effect of the harvest time and the ripening stages on a variety of plant species has been studied in different levels, chief among them: physiological maturity, [18] phytoconstituents quantity and quality, [19,20] biological activities. [21,22] Several studies dealt with the influence of seasonal harvest on P. atlantica Desf.…”
Section: Introductionmentioning
confidence: 99%
“…Although these constituents offer many substantial effects in human welfares, the biosynthesis of polyphenolic compounds attributed the biological activities may often modulate by various factors, which include cultivars, genotypes, environmental conditions, such as light intensity, relative humidity, and cultivation practices. Harvesting application as part of the cultivation practices has been known to have a significant role in influencing the quantitative and qualitative aspects in plants, resulting in an increment in growth, yield, and value of crops [ 30 , 31 , 32 , 33 , 34 , 35 ]. It is indeed shown that age-related factor has effectively enhanced the quantity and quality of the plant, specifically in phytochemical content and antioxidant activities in several crops [ 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%